Efektivitas Model Pembelajaran Koopertif Tipe Numbered Head Together (NHT) Berbantuan Game Number Chains Terhadap Kemampuan Berpikir Kritis Siswa - Putri, Putri Eka Pratiwi; Umbara, Uba (Polinomial : Jurnal Pendidikan Matematika, 2025)
Mathematics is a learning that requires students to keep thinking so that it can improve students' critical thinking skills. This study aims to determine the effectiveness of a cooperative learning model assisted by interactive media on students' critical thinking skills at SMK Negeri 1 Kuningan, using samples of X Grafika 1 and X Grafika 2 classes. This research is an experimental research using nonquivalent control group design. Before proving the hypothesis to determine the difference in the improvement of critical thinking skills between the experimental class and the control class, the normality and homogeneity test of the N-gain value of each class was carried out first. The normality test used is Shapiro wilk and results in Whitung < Wtabel so that the data is not normally distributed, because the prerequisite test is not met, the hypothesis test uses the Mann Whitney U nonparametric test. The results of this study show Zhitung> Ztabel then H0 is accepted which means there is a difference in students' critical thinking skills between the experimental class and the control class. This indicates that the use of cooperative learning models assisted by interactive game media is effective in improving students' critical thinking skills, besides the results of student response questionnaires which are quite positive also show that cooperative learning models assisted by interactive learning media are able to increase student involvement in the learning process.